The contribution of Verhnyatska Experimental Breeding station in the development of agricultural science and research activities in the first half of the 20th century - S. V. Nyzhnyk (History of science and technology, 2017)
Basing on historical and scientific analysis the author describes the main achievements of Verhnyatska Breeding station (now Cherkasy State Agricultural station of the NSC “Agricultural Institute NAAS of Ukraine”) in the first half of the 20th century. One of the important tasks of the station was to obtain stable and heavy crops in the region. The development of the material and technical base, the enhancement of the scientific staff gave the opportunity to improve the specialization of the breeding work, scientific research relating to the creation of new varieties of agricultural crops.